Menciptakan Sekolah Ramah Anak: Program Pengabdian Masyarakat dalam Meningkatkan Kesadaran Pendidikan Karakter di Sekolah Dasar Darul Ishlah - Muntoha, Tohir (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
An indication of the problem in this study is the lack of understanding and consistent implementation of character education at Darul Ishlah Primary School, which hinders the creation of an effective child-friendly school. The purpose of this study is to examine the implementation of the community service program in raising awareness about the importance of character education among teachers and parents, and to analyze its impact on students' character development. The research method used was a qualitative approach with a case study, involving observation, interviews and document analysis to extract information from teachers, parents and school officials regarding the implementation of this program. The findings showed that although there is an increased awareness of character education, the main challenges faced are the consistency of character implementation at school and home, as well as limited resources and support from parents. This study suggests the need for continuous efforts in involving all relevant parties to create a child-friendly learning environment that supports students' character development to the fullest.